Revisiting Ezra Pound: an ecofeminist approach to “The River-Merchant’s Wife: A Letter” - Shang, Jingmei; Mohsen, Hamoud Yahya Ahmed; Zhang, Hongmei; Wang, Jijun (Sciedu Press, 2024)
The paper focuses on one of intrinsic studies of literary works called ecofeminism. For the object of the current research, the author chooses one of Ezra Pound's poems, as is known to all, The River-Merchant’s Wife: A Letter. The author uses descriptive and analytic method in this paper. As is discussed, the author analyzes the potential ecofeminism by reading this poem carefully and giving a special attention for the lines that express and convey ecofeminism. Meanwhile, the author uses description and figure of speech analysis to build a concrete and poetic artistic conception in this poem. The findings suggest Ezra Pound spent a lot of conception and thinking on the description of environmental vision, including women and nature. On the one hand, the writing vision is tangible, evidenced by integrating his realistic living surroundings and the artistic conception in this poem. On the other hand, the expression of this poem is emotional, which, to a certain degree, evokes contemporary sensitivity to ecology and the concern on women, even the present social and environmental challenges, and the links between nature and literary that have become increasing obvious in the literary studies. The description of the natural surroundings of the poet prompts his deep awareness of environment, which can be looked upon as a potential ecofeminism.